Four weeks of electromyostimulation improves muscle function and strength in sarcopenic patients: a three‐arm parallel randomized trial. Issue 4 (9th June 2021) - Teschler, Marc; Heimer, Melina; Schmitz, Boris; Kemmler, Wolfgang; Mooren, Frank C.
Abstract: Background: Sarcopenia, defined as loss of muscle mass, quality, and function, is associated with reduced quality of life and adverse health outcomes including disability and mortality. Electromyostimulation (EMS) has been suggested to attenuate the loss of muscle mass and function in elderly, sedentary individuals. This study aimed to investigate the effects of EMS on muscle strength and function during 4 weeks of inpatient medical rehabilitation. Methods: Patients receiving 4 weeks of inpatient medical rehabilitation diagnosed with sarcopenia using bioimpedance analysis were eligible to participate. One hundred and thirty‐four patients (55.7 ± 7.9 years, 25.4% female) were randomly assigned to three groups: whole‐body (WB) EMS ( n = 48): stimulation of major muscle groups (pectoral muscles, latissimus, trapezius, abdominals, upper arm and leg, lower back muscles, gluteal muscles, and thighs); part‐body (PB) EMS ( n = 42): stimulation of leg muscles including gluteal muscles and thighs; and control group (CG, n = 44). All participants performed six 20 min training sessions including dynamic movements (squats, lunges, biceps curl, chest press, butterfly reverse, reverse lunges, standing diagonal crunches, etc.) with superimposed (WB‐, PB‐) EMS or without EMS (CG) in addition to the standard rehabilitation programme. Primary outcome variables included muscle function assessed by chair rise test and 6 min walking test as well as muscle strength (isometric grip strength, leg, arm, and back extension). Results: Primary outcome variables chair rise test and leg extension improved significantly ( P = 0.001, η 2 = 0.06 and P = 0.008, η 2 = 0.06; EMS vs. CG) in that chair rise test results increased in WB‐EMS from 5 (4; 7) to 7 (5; 9), in PB‐EMS from 5 (5; 7) to 7 (6; 8), and in CG from 6 (4; 7) to 7 (5; 8) repetitions. Knee extension increased in WB‐EMS from 692.3 ± 248.6 to 831.7 ± 298.7 N, in PB‐EMS from 682.8 ± 257.8 to 790.2 ± 270.2 N, and in CG from 638.5 ± 236.9 to 703.2 ± 218.6 N. No adverse events or side effects occurred. Conclusions: We conclude that EMS might be an additional training option to improve muscle function and strength in sarcopenic patients during a 4 week rehabilitation programme. EMS provides greater functional and strength improvements compared with standard treatment with additional potential health benefits for sarcopenic cardiac and orthopaedic patients.